(untitled) (World Science, 2021)
Ovarian tumors may be found in women of any age and the period of pregnancy is no exception. Besides, this period is related to some specific adnexal tumors. A systematic use of ultrasonography in the first trimester of pregnancy has led to a wider detection of symptomless adnexal tumors. The majority of adnexal tumors diagnosed during pregnancy are accidental findings of routine examinations of pregnancy. According to various estimations, the incidence of adnexal neoplasms during pregnancy makes up from 0.19 to 8.8 %. Most of cases are diagnosed in the first trimester and their incidence gradually decreases as the period of pregnancy grows: Trimester 1 – from 21.4 to 75.7 %; Trimester 2 – from 10.9 to 44.4 %; Trimester 3 – from 4 to 22.2 %; after labor – from 0 to 7.1 %. Most of adnexal tumors during pregnancy are benign and physiological and often regress spontaneously. Depending on their size and location, ovarian tumors may be related to an adverse obstetrical result caused by mechanical influence. They increase the risk of abortion (from 0 to 6 %), preterm labor (from 5.8 to 10.4 %) and mechanical impediment to labor. In view of the above mentioned considerations, one of the objectives of our research is to make a retrospective analysis of perinatal peculiarities in women with benign ovarian neoplasms.